Pengembangan Strategi Penyuluhan Agama Di Kantor Urusan Agama Untuk Meningkatkan Kesadaran Masyarakat Beragama Kecamatan Medan Perjuangan - Wahida Sitanggang; Siti Nur'aisyah; Siti Mawaddah; Wita Azani; Teuku Thareq Kemal; Hasnah Nasution (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Increasing awareness of religious communities is one of the main tasks carried out by the Office of Religious Affairs (KUA) in Medan Perjuangan District. This research aims to develop an effective and sustainable religious outreach strategy to increase public understanding and awareness of religious values in everyday life. The research approach uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation. The research results show that religious counseling that is participatory and based on community needs is more effective in creating changes in religious behavior. The proposed strategy includes strengthening the role of religious instructors as facilitators, preparing programs based on specific community problems, and using digital media to expand educational reach. By implementing this strategy, it is hoped that public awareness of the importance of religious values will increase, thus supporting the creation of social harmony and a better religious life.